The Influence of SI-RS Development and Computer Self-Efficacy on the Implementation of EMR Mediated by Barrier Self-Efficacy at Firdaus Hospital - Erish Harry Angkat; MF. Arrozi Adhikara; Wahyuni Dian (Jurnal Cinta Nusantara, 2023)
Health technology transformation is realized through development and utilization technology, digitalization, as well as bio-technology. The implementation of health technology transformation that has been carried out by the Ministry of Health is the enactment of Minister of Health Regulation Number 24 of 2022 concerning Medical Records which requires all hospitals to maintain electronic medical records (EMR) no later than 31 December 2023. The aim of this research namely to analyze the influence of the development of SI-RS and computer self-efficiency on the implementation of EMR which is mediated by self-efficacy barriers at Firdaus Hospital. The research method used is an associative quantitative research method. This research was conducted on medical service and examination officers with a population of 261 people. The sample used was 110 people who were calculated proportionally. This research uses path analysis and regression analysis techniques. The results of this study indicate that the simultaneous development of SI-RS and computer self-efficiency have an effect on the implementation of EMR which is mediated by self-efficacy barriers, partial development of SI-RS has no effect on self-efficacy barriers, computer self-efficiency partially influences barrier self-efficacy, barrier self-efficacy partially influences EMR implementation, SI-RS development partially influences EMR implementation, and computer self-efficacy partially influences EMR implementation.